EFFECT OF NAA AND BAP APPLICATION ON THE GROWTH RESPONSES OF Mentha × piperita L. - Nur Rahmawati Wijaya; Devi Safrina; Prambayu Brenda Herera; Mery Budiarti (Jurnal Tumbuhan Obat Indonesia, 2022)
Mentha × piperita L., also known as peppermint, is a plant with various uses, including medicine, cosmetics, and food. Numerous industries have a high need for peppermint products, but Indonesia is currently unable to meet this demand and should continue to import peppermint. One effort can be made to improve cultivation procedures, and tissue culture becomes one alternative. This research uses shoots as explants with Murashige & Skoog's basic media and growth regulators BAP and NAA. The research was conducted in two phases: six-week initial planting and seven-week subculture. The treatment of BAP 4 mg/L + NAA 0.5 mg/L provides better performance for the number of leaves, and BAP 3 mg/L produced the best response regarding the number of shoots. Furthermore, BAP 1 mg/L + NAA 1 mg/L produced the best response to shoot height and number of leaves, and BAP 3 mg/L + NAA 0.5 mg/L generated the best response to root length. Based on the research, BAP 3 mg/L is the optimal treatment.